A strenuous experimental journey searching for spectroscopic evidence of a bridging nickel–iron–hydride in [NiFe] hydrogenase - Wang, Hongxin (J Synchrotron Radiat, 2015)
Direct spectroscopic evidence for a hydride bridge in the Ni–R form of [NiFe] hydrogenase has been obtained using iron-specific nuclear resonance vibrational spectroscopy (NRVS). The Ni–H–Fe wag mode at 675 cm(−1) is the first spectroscopic evidence for a bridging hydride in Ni–R as well as the first iron-hydride-related NRVS feature observed for a biological system. Although density function theory (DFT) calculation assisted the determination of the Ni–R structure, it did not predict the Ni–H–Fe wag mode at ∼675 cm(−1) before NRVS. Instead, the observed Ni–H–Fe mode provided a critical reference for the DFT calculations. While the overall science about Ni–R is presented and discussed elsewhere, this article focuses on the long and strenuous experimental journey to search for and experimentally identify the Ni–H–Fe wag mode in a Ni–R sample. As a methodology, the results presented here will go beyond Ni–R and hydrogenase research and will also be of interest to other scientists who use synchrotron radiation for measuring dilute samples or weak spectroscopic features.